STUDENTS’ ERROR IN USING SIMPLE PRESENT TENSE - Horia Siregar; Melisa Zuriani (PROJECT (Professional Journal of English Education), 2020)
This research aimed to analyse the errors in using simple present tense. Descriptive qualitataive approach was used in this reserch. The subject of this research was 37 management students of Economic Faculty  Muslim Nusantara Al Washliyah University  Medan. The data were the sudents’  answer test.  This research was analysed by Surface strategy taxonomy proposed by Dulay et al. The results of the research showed that there are four types of students’ errors in using simple present tense. These errors are categorized into omissions, additions, misinformation, and misordering. The most errors made by students is  omission with 50,61%,and the lowest is misordering with  2,47%. Keywords:  Error Analysis, Simple Present Tense, Types of Error